Identifikasi Rimpang Temulawak (Curcuma xanthorriza) dalam Jamu Pegal Linu Secara Kromatografi Lapis Tipis (KLT) - Amin, Asni; Rahmadani, Fitri; Syarif, Rezki Amriati (Makassar Pharmaceutical Science Journal (MPSJ), 2024)
Indonesia's biodiversity that exists around its community environment has been used for generations as a food and medicinal ingredient, one of which is temulawak (Curcuma xanthorriza.). Temulawak is used as a raw material for herbal aches and pains because it is efficacious to help reduce or eliminate inflammatory diseases in the body such as arthritis. The purpose of this study was to identify the presence of curcuma content in several aching and rheumatic herbs using an experimental design. The method used was a qualitative test using thin layer chromatography (TLC) with n-hexane -acetone as the mobile phase (6:4). The results of TLC observations at 254 nm and 366 nm UV lamps showed yellow spots on the comparator temulawak simplicia and the Rf value of the curcuma simplicia was 0.690. The results of the identification of the five samples of herbal medicine stiff and sore by TLC proved to contain temulawak simplicia.